Exploring the effects of gut microbiota on cholangiocarcinoma progression by patient-derived organoids - Ann-Kathrin Lederer; Nele Görrissen; Tinh Thi Nguyen; Clemens Kreutz; Hannah Rasel; Fabian Bartsch; Hauke Lang; Kristina Endres (Journal of Translational Medicine)
Abstract Background Recent research indicates a role of gut microbiota in development and progression of life-threatening diseases such as cancer. Carcinomas of the biliary ducts, the so-called cholangiocarcinomas, are known for their aggressive tumor biology, implying poor prognosis of affected patients. An impact of the gut microbiota on cholangiocarcinoma development and progression is plausible due to the enterohepatic circulation and is therefore the subject of scientific debate, however evidence is still lacking. This review aimed to discuss the suitability of complex cell culture models to investigate the role of gut microbiota in cholangiocarcinoma progression. Main body Clinical research in this area is challenging due to poor comparability of patients and feasibility reasons, which is why translational models are needed to understand the basis of tumor progression in cholangiocarcinoma. A promising approach to investigate the influence of gut microbiota could be an organoid model. Organoids are 3D cell models cultivated in a modifiable and controlled condition, which can be grown from tumor tissue. 3D cell models are able to imitate physiological and pathological processes in the human body and thus contribute to a better understanding of health and disease. Conclusion The use of complex cell cultures such as organoids and organoid co-cultures might be powerful and valuable tools to study not only the growth behavior and growth of cholangiocarcinoma cells, but also the interaction with the tumor microenvironment and with components of the gut microbiota.